Vertical Ge and GeSn heterojunction gate-all-around tunneling field effect transistors. (August 2015) - Schulze, Jörg; Blech, Andreas; Datta, Arnab; Fischer, Inga A.; Hähnel, Daniel; Naasz, Sandra; Rolseth, Erlend; Tropper, Eva-Maria
Abstract: We present experimental results on the fabrication and characterization of vertical Ge and GeSn heterojunction Tunneling Field Effect Transistors (TFETs). A gate-all-around process with mesa diameters down to 70 nm is used to reduce leakage currents and improve electrostatic control of the gate over the transistor channel. An ION  = 88.4 μA/μm at VDS  =  VG  = −2 V is obtained for a TFET with a 10 nm Ge0.92 Sn0.08 layer at the source/channel junction. We discuss further possibilities for device improvements.